The evolution from surface‐ to bubble dynamics‐dominant growth mechanisms of synchronized bubble‐templated microporous copper. Issue 5 (18th May 2021) - Lin, Cheng‐Hui; Won, Yoonjin
Abstract: Background: Three‐dimensional porous structures have been widely utilized in numerous applications as porous structures can offer the unique combination of thermal and structural properties. While various porous structures can be fabricated through templated‐electrodeposition methods by employing sacrificial structures, an approach using bubbles as sacrificial templates is suggested to provide quasi‐random porous structures in a rapid and synchronized fashion. Aims: Despite their advantages, it has been challenging to engineer the morphological details because of the intrinsic nature of dynamic and ever‐changing bubbles. In this paper, we study the growth mechanisms of bubble‐templated porous copper depending on the combination of surface profiles and deposition time. Results: We reveal the evolution from surface‐ to bubble dynamics‐governing growth mechanisms by quantifying quasi‐random characteristics of biporous copper through their electron microscopic images and spectral density functions.